MODERN TEACHING METHODS IN LANGUAGE EDUCATION - Turayeva Diyora Khayrullayevna (XALQARO ILMIY-AMALIY ANJUMAN "TA'LIM MAYDONI TENDENSIYALARI: KOMPETENTSIYALAR, INNOVATSIYALAR VA TEXNOLOGIYALAR", 2025)
This article examines contemporary approaches to language education, emphasizing the shift from traditional, grammar-focused instruction to more interactive, student-centered methods. It highlights strategies such as Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), and the integration of digital tools that enhance learner engagement and effectiveness. With an increased focus on real-life communication, cultural competence, and learner autonomy, modern teaching methods aim to create dynamic and inclusive learning environments. The article also discusses the role of technology and the importance of adapting instruction to meet diverse student needs. Ultimately, it advocates for innovative practices that prepare learners for meaningful language use in global contexts.